The NUMEN Project: An Update of the Facility Toward the Future Experimental Campaigns - Cappuzzello, Francesco; Acosta, Luis; Agodi, Clementina; Boztosun, Ismail; Brischetto, Giuseppe A.; Calabrese, Salvatore; Calabretta, Luciano; Calvo, Daniela; Campajola, Luigi; Capirossi, Vittoria; Carbone, Diana; Cavallaro, Manuela; et al. (Frontiers in Astronomy and Space Sciences, 2021)
The goal of NUMEN project is to access experimentally driven information on Nuclear Matrix Elements (NME) involved in the neutrinoless double beta decay (0νββ) by accurate measurements of the cross sections of heavy-ion induced double charge-exchange reactions. In particular, the (18O, 18Ne) and (20Ne, 20O) reactions are adopted as tools for β+β+ and β−β− decays, respectively. The experiments are performed at INFN–Laboratory Nazionali del Sud (LNS) in Catania using the Superconducting Cyclotron to accelerate the beams and the MAGNEX magnetic spectrometer to detect the reaction products. The measured cross sections are very low, limiting the present exploration to few selected isotopes of interest in the context of typically low-yield experimental runs. In order to make feasible a systematic study of all the candidate nuclei, a major upgrade of the LNS facility is foreseen to increase the experimental yield by more than two orders of magnitude. To this purpose, frontier technologies are being developed for both the accelerator and the detection systems. An update description of the NUMEN project is presented here, focusing on recent achievements from the R&D activity.